Analysis of web tracking and geolocation of German-language health websites. - Patrick Siegle; Monika Pobiruchin; Richard Zowalla (PLoS ONE)
Nowadays, websites with health-related content are an essential source of information for consumers to find out about their diagnoses, therapies, but also about prevention aspects. The data protection of website visitors is of particular interest here, as the search for health information may allow conclusions to be drawn about their own illnesses or those of their relatives. With a main focus on privacy-relevant aspects, this study examines more than 231,000 German-language health websites from Germany, Austria, and Switzerland. Of all successfully visited websites 56.04% stored at least one cookie. Up to 18.93% of the websites contained cookies that were not technically necessary and were set without explicit consent. The geolocation analysis revealed that among 16.30% of resolved hostnames, at least one IP address was detected that was not from the country suggested by the top-level domain.